2015
DOI: 10.1097/ico.0000000000000550
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Primary Collagen Cross-Linking with Photoactivated Chromophore (PACK-CXL) for the Treatment of Staphylococcus aureus–Induced Corneal Ulcers

Abstract: We demonstrate a beneficial effect of PACK-CXL as primary treatment, either as stand-alone or as an adjuvant to antimicrobial therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 27 publications
0
12
0
4
Order By: Relevance
“…As microbial resistance to antibiotics increases, new lines of treatment will be needed and thus CXL may be a promising alternative or adjunct to current therapy. Both a recent animal study [84] using S. aureus induced ulcers in the rabbit as a model and a study involving 32 patients with moderate bacterial corneal ulcers [85] provide positive data to support this tenet. In fact, in the patient study, CXL treatment accelerated epithelial healing and shortened treatment time.…”
Section: New Frontiers In Treatmentmentioning
confidence: 93%
“…As microbial resistance to antibiotics increases, new lines of treatment will be needed and thus CXL may be a promising alternative or adjunct to current therapy. Both a recent animal study [84] using S. aureus induced ulcers in the rabbit as a model and a study involving 32 patients with moderate bacterial corneal ulcers [85] provide positive data to support this tenet. In fact, in the patient study, CXL treatment accelerated epithelial healing and shortened treatment time.…”
Section: New Frontiers In Treatmentmentioning
confidence: 93%
“…evaluated the efficacy of corneal CXL as primary therapy for S. aureus corneal ulcer in rabbit model. [22] Forty rabbits were randomly assigned to four groups: group-A: No treatment (control); Group-B: Topical antibiotic treatment (cefazolin 50 mg/mL, Garamycin 14 mg/mL drops, and chloramphenicol 5% ointment every 2 h); Group-C: CXL; and Group-D: CXL + topical antibiotics. After 1 month of treatment, Group-C ulcers had the smallest mean scar diameter and shortest mean healing time.…”
Section: Are These Results Translated In In Iivo Animal Experiments?mentioning
confidence: 99%
“…Despite numerous clinical reports with promising results after use of PACK‐CXL, there are few controlled trials regarding the outcome of CXL treatment compared to antibiotic treatment alone for infectious keratitis . CXL research in animals has mainly been performed experimentally, Tal et al compared CXL treatment alone, medical treatment alone, CXL + topical antibiotics to no treatment in rabbits with corneal ulcers infected with Staphylococcus aureus. The authors concluded that CXL had a positive effect both as stand‐alone treatment and in combination with medical therapy.…”
Section: Discussionmentioning
confidence: 99%